House of Gucci - Forden, Sara Gay (New York HarperCollins Books, 2021)
On March 27, 1995, Maurizio Gucci, heir to the fabulous fashion dynasty, was slain by an unknown gunman as he approached his Milan office. In 1998, his ex-wife Patrizia Reggiani Martinelli$1 (Bnicknamed (3z(BThe Black Widow(3y (Bby the press$1 (Bwas sentenced to twenty-nine years in prison, for arranging his murder. Did Patrizia murder her ex-husband because his spending was wildly out of control? Did she do it because her glamorous ex was preparing to marry his mistress, Paola Franchi? Or is there a possibility she didn$1 (Bt do it at all? The Gucci story is one of glitz; glamour; intrigue; the rise, near fall, and subsequent resurgence of a fashion dynasty. Beautifully written, impeccably researched, and widely acclaimed, The House of Gucci will captivate readers with its page-turning account of high fashion, high finance, and heart-rending personal tragedy.s
Keywords: A True Story